2017
DOI: 10.1002/dvdy.24482
|View full text |Cite
|
Sign up to set email alerts
|

Hox genes in the adult skeleton: Novel functions beyond embryonic development

Abstract: Hox genes encode evolutionarily conserved transcription factors that control skeletal patterning in the developing embryo. They are expressed in regionally restricted domains and function to regulate the morphology of specific vertebral and long bone elements. Recent work has provided evidence that Hox genes continue to be regionally expressed in adult tissues. Fibroblasts cultured from adult tissues show broadly maintained Hox gene expression patterns. In the adult skeleton, Hox genes are expressed in progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 96 publications
2
70
1
1
Order By: Relevance
“…The Hox family of transcription factors play an important role in the patterning of tissue during development, and some of the Hox genes continue to be expressed in tissues after development (Pineault & Wellik, 2014; Rux & Wellik, 2017). The posterior Hox genes ( Hox9‐13 ), which are involved in patterning of the limb skeleton along the proximodistal axis, were highly expressed in the four tendon types we evaluated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Hox family of transcription factors play an important role in the patterning of tissue during development, and some of the Hox genes continue to be expressed in tissues after development (Pineault & Wellik, 2014; Rux & Wellik, 2017). The posterior Hox genes ( Hox9‐13 ), which are involved in patterning of the limb skeleton along the proximodistal axis, were highly expressed in the four tendon types we evaluated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(26)(27)(28) Importantly, we reported that the adult expression and function of Hox11 genes is spatially restricted to same region in which these genes are expressed and function in the embryo (the zeugopod for Hox11 in the limb skeleton), and that other adult Hox gene expression profiles also follow this pattern in other regions of the skeleton. (25,29) Together, this work suggests that Hox genes are expressed and function with regional specificity in adult skeletal MSCs.…”
Section: Introductionmentioning
confidence: 70%
“…Using a Hoxa11eGFP insertion allele, we demonstrated that Hoxa11eGFP+ cells are exclusively expressed in PDGFRα+, CD51+, and Leptin Receptor+ (LepR+) cells, markers that have been previously characterized to enrich for mesenchymal progenitor activity in bone marrow non‐endothelial stroma and to contribute to fracture healing . Importantly, we reported that the adult expression and function of Hox11 genes is spatially restricted to same region in which these genes are expressed and function in the embryo (the zeugopod for Hox11 in the limb skeleton), and that other adult Hox gene expression profiles also follow this pattern in other regions of the skeleton . Together, this work suggests that Hox genes are expressed and function with regional specificity in adult skeletal MSCs.…”
Section: Introductionmentioning
confidence: 97%
“…Hox gene expression is critical during skeletal patterning and postnatal bone formation (1)(2)(3). A majority of research in vertebrates has shown that Hox-regulating miRNAs are encoded within the four Hox clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian homeobox (Hox) 3 developmental transcription factors have diverse roles in bone development and postnatal bone formation (1)(2)(3). These roles include skeletal element formation (4), anterior-posterior homeotic development (4 -10), and limb and axial skeleton formation (11)(12)(13)(14)(15).…”
Section: Micrornas (Mirs) and Hox Transcription Factors Have Decisivementioning
confidence: 99%